Local Anaesthetic Infiltration and Indwelling Postoperative Wound Catheters for Patients with Hip Fracture Reduce Death Rates and Length of Stay. (16th November 2015) - Harrison, William D.; Lees, Deborah; A'Court, Jamie; Ankers, Thomas; Harper, Ian; Inman, Dominic; Reed, Mike R.
Abstract : Background . An analgesic enhanced recovery (ER) protocol for patients with a hip fracture was introduced. It was hypothesised that the ER would reduce pain, length of stay and improve clinical outcomes. The protocol used intraoperative infiltration of levobupivacaine followed by ongoing wound infusions. Methods. Consecutive patients admitted to two hospitals were eligible for the ER protocol. Numerical Reporting Scale pain scores (0–10) were recorded alongside opiate requirements. 434 patients in the ER group (316 full ER, 90 partial ER, and 28 no ER) were compared to a control group (CG) of 100 consecutive patients managed with traditional opiate analgesia. Results . Mean opiate requirement was 49.2 mg (CG) versus 32.5 mg (ER). Pain scores were significantly reduced in the full ER group, p < 0.0001 . Direct discharge home and mean acute inpatient stay were significantly reduced (p = 0.0031 andp < 0.0001, resp.). 30-day mortality was 15% (CG) versus 5.5% (ER), p = 0.0024 . Conclusions . This analgesic ER protocol for patients with a hip fracture was safe and effective and was associated with reduced inpatient stay and mortality.